Detection of Spargana on Ptyas korros in Sidoarjo - Bagaskara, Ryan; Lukiswanto, Bambang Sektiari; Rahardjo, Adi Prijo; Poetranto, Emmanuel Djoko; Koesdarto, Setiawan; Mufasirin, Mufasirin (Jurnal Medik Veteriner, 2023)
Ptyas korros or Indo-China Rat Snake is one of the snakes that are commonly hunted in Indonesia. This study aimed to identify Spirometra sp. on P. korros in Sidoarjo. A total of 18 snakes were collected within 3 months. Identification of Spirometra sp. was done using a native method, Semichen Acetic Carmine, and HE staining. As a results, 8 (44.4%) of 18 samples showed positive infection with Spirometra sp. The results of this study indicate the presence of spargana in P. korros in Sidoarjo and no adult Spirometra sp. was found.